Small exponent asymptotics - Fowler, A; Kember, G; O'Brien, S (Oxford Univ Press, 2000)
We study the surprisingly complicated asymptotic character of a simple first-order differential equation, which involves a term with a low exponent of the dependent variable. While numerical solutions and straightforward asymptotic expansions indicate a clearly defined boundary layer type transition, we find that the correct asymptotic structure involves a 'hidden' boundary layer, and that a straightforward approach cannot discern this.